A revision of bupresticida species group of Cerceris Latreille, 1802 (Hymenoptera: Crabronidae: Philanthinae) of the Western Palearctic region, with the description of Cerceris ammonia, a new species from Egypt - Malash, Alyaa A.; Edmardash, Yusuf A.; Gadallah, Neveen S. (Zootaxa, 2024)
A total of six species of the Cerceris bupresticida group have been studied, of which C. ammonia Malash, Edmardash & Gadallah is described and illustrated as a new species. Distribution data, as well as taxonomic comments are given for each species. Illustrations of different body parts are provided for all species under study. An illustrated key to all species of this group is also provided.